PENGEMBANGAN MEDIA AUGMENTED REALITY PADA MATERI VOLUME BANGUN RUANG DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN BATURNO - Nur Aulia Agustina; Wendri Wiratsiwi (ELENOR: Elementary School Journal, 2024)
Abstract. The problem in class V SDN Baturno is the low academic achievements of students, particularly in Mathematics. The main factor is the lack of use of innovative learning media, by developing augmented reality media is expected to overcome this problem. The formulation of the problem in this study describes the development process, the level of validity, the level of practicality and the effectiveness of augmented reality media. This study aims to describe the development process, determine the level of validity, level of practicality and effectiveness of augmented reality media. The method used in this research is the development method or Research and Development (R&D) with the ADDIE model. The development procedure in this study includes analysis, design, development, implementation, and evaluation which refers to Robert Maribe Branch. Based on the results of material expert validation getting a percentage of 95.45%, the augmented reality media developed in the criteria is very valid for use.  Media expert validation gets a percentage score of 97.72% stated that augmented reality media is stated in very valid criteria to be developed.  The level of effectiveness is measured by a test sheet which is found from 12 students there are 10 students who are complete. Student learning outcomes have progressed very rapidly compared to the daily test which only 1 student completed the KKTP. It can be concluded that the augment media.